Development of an IoT based weighing type micro-lysimeter for soilless cultivation - GOYAL, POOJA; SHARDA, RAKESH; SIAG, MUKESH; SINGH, K G (The Indian Journal of Agricultural Sciences, 2020)
In the present study, an attempt has been made to apply Internet of Things (IoT) for precise irrigation management. A weighing type micro-lysimeter based on IoT was developed to measure the amount of water consumed by the cucumber crop grown in soilless media under naturally ventilated greenhouse conditions at the Research Farm of Punjab Agricultural University, India. The developed system consisted of two components, i.e. hardware assembly and web-based application. The hardware assembly consists of load cells, a weight sensing module, i.e. HX711 module and a micro controller, i.e. arduino assembled in the control box of the weighing balance. A modular code was written in arduino to record the weight readings. The stored data in the microcontroller was sent to a web based application via wifi. The weight changes at the lysimeters due to irrigation, drainage and evapotranspiration were monitored in real time through an IoT platform, i.e. Thingspeak. Three lysimeters were placed at different locations to account for the slight variations in micro-climate within the greenhouse. The positive flux i.e. irrigation and negative flux, i.e. (leachate+ actual evapotranspiration (ETc)) from the lysimeter were derived from the IoT platform. Irrigation and leachate from the lysimeter was also measured manually to verify the accuracy of the readings obtained from the IoT platform. The study showed that IoT based lysimeters presents a reliable and convenient way to measure ETc as there was a good agreement (R2> 0.98) between irrigation component derived from IoT and actual irrigation applied.